Flipping the English grammar classroom: a pedagogical experiment for undergraduate students - Pacheco-Franco, Marta (My University, 2022)
Grammar is a key component of any language teaching curriculum, whether it ascribes to structural or to communicative approaches (Ur 2012). Although the attention devoted to grammar has decreased in the latter models ‒mainly because other components have gained relevance‒, students continue to dread grammar lessons. These are infamous for being long and boring, since they typically consist of a lecture from the teacher and are followed by some drill-type activity (Larsen-Freeman 2001). Despite the myriad of pedagogical innovations today, this continues to be the state of affairs in grammar teaching, more so at university level. Indeed, the role of the lecture in undergraduate teaching seems to be irreplaceable, or almost so (Reidsema et al. 2017). The flipped classroom is an educational model that is gaining ground today by challenging the basis of this type of presentation (Kvashnina and Martynko 2016). It provides students with a blended learning experience that affects both the medium and the temporality of teaching, since flipped classrooms often present a combination of asynchronous online learning and synchronous face-to-face lessons (Reidsema et al. 2017). However, the model is best characterised by the way the contents are presented and practiced. Whereas lecturing is the central activity in a traditional classroom and practice is assigned as homework, a flipped classroom does exactly the opposite (Bergmann and Sams 2012). In moving the “information-transmission teaching out of [the grammar] class” (Abeysekera and Dawson 2014: 4), the flipped model enables students to become active and independent in their learning process (Bergmann and Sams 2012: 16). If applied to the grammar lesson, a flipped classroom has the potential of involving students in the contents they are learning and of making this learning more significant (Abeysekera and Dawson 2014).
Keywords: Inglés - Gramática; Enseñanza superior; Flipped classroom; English grammar; Higher education; Motivation; Grammatical competence